Micelles: Rod‐to‐Globule Transition of pDNA/PEG–Poly(l‐Lysine) Polyplex Micelles Induced by a Collapsed Balance Between DNA Rigidity and PEG Crowdedness (Small 9/2016). Issue 9 (1st March 2016) - Tockary, Theofilus A.; Osada, Kensuke; Motoda, Yusuke; Hiki, Shigehiro; Chen, Qixian; Takeda, Kaori M.; Dirisala, Anjaneyulu; Osawa, Shigehito; Kataoka, Kazunori
Abstract : Upon PEG removal, the change of rod shapes into globule shapes is observed for packaged DNA in polyplex micelles that are prepared from block copolymers with acid‐labile linkage between the PEG and poly(L‐lysine) (PLys). On page 1193, K. Osada, K. Kataoka, and co‐workers use the details of this transition behavior to elucidate the essential regulating factors of polyplex micelle structures, in order to find their structure–function relationship and promote their utilization as a gene delivery system.